The effect of wadiah product quality attributes on customer satisfaction: the case of Jaiz Bank Nigeria Plc - Baba, Bashir; Mohamed Zabri, Shafie; Kaseri, Ahmad (Galore Knowledge Publication Pvt. Ltd, 2018)
Islamic banks offer services based on the dictates of Shari’ah law, which advocates for the system of banking void of oppression of any of the contracting parties through the abolition of interest (Ribaa). This study aims at investigating the level of customer satisfaction on one of the Islamic bank products (Wadi’ah) and to examine the relationship between the product’s characteristics and customer satisfaction. The study adopted the Kano theory of customer satisfaction using four characteristics of the products (perceived quality, Cost, Convenience and Compliance). The quantitative technique of data collection was adopted using a questionnaire to gather information from the customers of the Islamic bank, and Partial Least Square (PLS-SEM) was used in the data analysis. The results show that the satisfaction level of perceived quality of Wadi’ah product was found to be moderate, and the cost of maintaining Wadiah account has its satisfaction level as high, the result also show that customers were satisfied in using the Wadi’ah product with convenience, and in the case of compliance, the customers were satisfied that the activities in Wadiah were in line with the principles of Shari’ah.